INTRODUCTION TO MATHEMATICAL FIGURES FOR CHANGING POWER LEARNING MATHEMATICS FOR VOCATIONAL SCHOOL STUDENTS - Nashrullah Mailisman; Nailul Authary; Nazariah Nazariah; Fitriyasni Fitriyasni; M. Alfarisyi (Universitas Muhammadiyah Aceh, 2024)
Applying the history of mathematics in learning is a tool (history as a tool) or strategy for building meaningful and value-laden learning. Nowadays, we often encounter mathematics learning that only emphasizes the use of formulas without paying attention to the beneficial aspects of the material being taught. Educators argue that students must achieve material targets according to predetermined bills. The result is that children study mathematics for years but are still